Congenital Rubella Syndrome-a Case Report with Clinical Manifestation and Management Approach (Journal of National Institute of Ophthalmology, 2023)
Congenital rubella syndrome (CRS) is an illness in infant resulting from maternal infection with rubella virus during pregnancy. Patients suffer from some complications included deafness, cataract, heart defects, mental retardation, bone alterations, liver and spleen damage. Purpose of this study is to create attention, early identification and keep special concern in management of such case. A 15 years old girl presented with dimness of vision since childhood. Her mother had a history of fever and skin rash during prenatal period. She had mental retardation, deafness, dumbness, thin stature, microchephaly. Unaided vision fixed and follows in both eyes. Anterior segments showed bilateral microphthalmos, nystagmus, microcornea, aphakia.  Intraocular pressure was 40 mm of Hg in each eye. Color fundus photograph showed myopic crescent with tessellated fundus. Echocardiogram showed pulmonary stenosis. Ultrasonography whole abdomen revealed chronic hepatitis. LDH level was 380 units/L. She had hyperthyroidism. Her sensory neural hearing loss was detected by audiometry. She was referred to glaucoma clinic for raised ocular pressure; low vision clinic for visual rehabilitation; medicine specialist for cardiac problem, liver problem and hormonal imbalance. All presenting features revealed that it was a case of congenital rubella syndrome as the girl had deafness, cardiac problem and ocular abnormality which are triad of CRS. Early diagnosis, timely management and proper counseling to patient and guardian will consequently increase life quality of this patient. National awareness should be increased for full coverage of antenatal check up with MMR vaccination in all health care centers of developing countries.J.Natl.Inst.Ophthalmol.2023;6(1): 54-59